2009
DOI: 10.1016/j.disc.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Product irregularity strength of graphs

Abstract: a b s t r a c tConsider a simple graph G with no isolated edges and at most one isolated vertex. AThe goal is to obtain a product-irregular labeling that minimizes the maximum label. This minimum value is called the product irregularity strength. The analogous concept of irregularity strength, with sums in place of products, has been introduced by Chartrand et al. and investigated by many authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…The concept was introduced by M. Anholcer in [4]. As we can see, it is the multiplicative version of the well known irregularity strength introduced by Chartrand et al in [5] and studied by numerous authors (the best result for general graphs can be found in Kalkowski, Karoński and Pfender [6], while e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The concept was introduced by M. Anholcer in [4]. As we can see, it is the multiplicative version of the well known irregularity strength introduced by Chartrand et al in [5] and studied by numerous authors (the best result for general graphs can be found in Kalkowski, Karoński and Pfender [6], while e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The two last results hold also for paths P n and all the Hamiltonian graphs of order n. In the same paper upper bounds for grids and toroidal grids were given. Theorem 1.10 ( [3]) For every ε > 0 there exist n (0) j ,j = 1, . .…”
Section: Proposition 14 ([20])mentioning
confidence: 99%
“…This concept was first introduced by Anholcer in [1] as a multiplicative version of the well-studied concept of irregularity strength of graphs introduced by Chartrand et al in [4] and studied later quite extensively (see for example [3,7,8,11]). A concept similar to product-irregular labelling is the product anti-magic labeling of a graph, where it is required that the labeling ω is bijective (see [9,12]).…”
Section: Introductionmentioning
confidence: 99%
“…In [1] Anholcer gave upper and lower bounds on product irregularity strength of graphs. The main results in [1] are estimates for product irregularity strength of cycles, in particular it was proved that for every n > 2…”
Section: Introductionmentioning
confidence: 99%